Enhancing Interoperability and Response Coordination in Disaster Settings: A Review of Methodological Frameworks and Technique (American Journal of Medical Science and Innovation, 2024)
When mobile field hospitals are deployed for disaster response missions, they face several challenges. Notable among the challenges is the lack of interoperability with the regional hospitals which is essential for patient information sharing and transfer when the need arises. Several healthcare systems around the globe have interoperability platforms that are well in place. However, due to different standards and system design they cannot easily interoperate with one another. This is even more apparent when interoperability during disaster response is desired between a mobile field hospital and regional hospital. The several interoperability frameworks designed by vendors are mainly designed for usage in large stationary hospitals, hence there is need to consider frameworks that can enhance interoperability between a mobile field hospital and regional hospital to facilitate coordinated disaster response. In this article we argue that an effective disaster response interoperability framework should be adaptable, affordable, simple to use, and capable of being employed in isolated, harsh environments such as occurs during disaster response. An analysis of several healthcare interoperability frameworks is conducted in this article with the aim of proposing a suitable framework for possible adoption by mobile field hospital’s interoperability with regionals hospitals during sudden onset disasters.